A Study on Customer Satisfaction towards Online Shopping: Exploring Factors Influencing Consumer Satisfaction in Online Shopping (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This research dubbed The Consumers online purchasing choices has been conducted in order to explain the causes. The exponential growth of the Internet strongly affects the global marketing climate. It has now become one of the common ways to trading over the internet by company and customers. Businesses also created forms for their goods to be promoted online. This reflects the replacement of the existing economy by the new sector. The aim of this analysis is to determine the variables that may affect the satisfaction of the consumer. In general, consumer loyalty in buying is important for the growth of online shopping.